Influence Of Third-Party Funds, Opertional Risk, Loan Banco Nasional Do Comersio De Timor Leste (Bnctl) Dili Timor-Leste - Ezaquiel Ribeiro de Jesus (LPPM Institut Teknologi dan Sains Mandala, 2022)
The research aims to determine the effect of third-party funds, operational risks, and loan to deposit ratios on profitability on Banco Nasional do Comércio de Timor-Leste (BNCTL). The method used is quantitative descriptive analysis. This type of data is Secondary data source from bank BNCTL's financial statements for the period 2010-2018, consisting of balance sheet statements and loss / profit statements. In this study, researcher conducted observations on financial statement data through annual reports provided by BNCTL for the period 2010-2018, thus getting nine years of observation. After secondary data is collected and analyzed then, tested using multiple linear regression analysis models. This analysis model consists of a normality test, an autocorrelation test, a multicollinearity test, and a regression model determination test. Based on the results of the analysis found, the results of the study showed that the variables DPK, BOPO and LDR, positively and significantly influential.